Possibilities of Cooperation between Teachers and Parents Cultivating Preschool Children’s Communication Competence at Kindergarten: Teachers’ Opinion - Turauskienė, Erika; Braslauskienė, Rasa (Vilnius University Open Series, 2020)
The object of educating preschool communication competence is relevant for good communication skills ensuring a successful person’s activity in a society, motivating social integration and an ability to exchange information. This is why parents and educators, who understand that preschool education should proceed both in a family and in a kindergarten, encouraging children to be interested in listening, speaking, writing, reading, should collaborate. In educators’ opinion, effective collaboration between parents and educators makes it possible to develop the following competences of communication: (a) to learn benevolent communication with adults and peers; (b) to get acquainted with letters; (c) to acquire active listening skills; (d) to improve the joining of sounds and letters, and the ability to speak in the mother tongue, etc.
Keywords: cooperation; education; communication competence; preschool age